Issues in the late payment due to Covid-19 pandemic - Rahmat, Norazlina (2022)
Delay or late payment in the construction project is a common phenomenon and has become a habit in the construction industry. However, in the year 2020, the pandemic of Coronavirus (COVID-19) has dramatically spread over the world. Due to COVID-19 Pandemic, the issue of late payment becomes worse and critical. Many parties involved in the project was affected especially the contractor. In line with the issue, the aim of this research is to identify the strategies to overcome the late payment issues due to the pandemic COVID-19 in the construction industry. The objectives of this research are to identify the factor that can lead to the late payment during the pandemic COVID-19, to determine the implication of late payment to the contractor due to pandemic COVID-19 and to suggest the potential strategies to overcome the late payment issue due to pandemic COVID-19. This research used quantitative approach through the distribution of questionnaire survey to the G6 Contractor that focusing on Petaling district. All the data collected have analysed using descriptive statistical analysis in the Statistical Package for the Social Sciences (SPSS) software. At the end of the research, the findings shows that the suspension of work during Movement Control Order (MCO) is the main factor that lead to the late payment during the pandemic COVID-19.